To pay or not to pay: An exploratory analysis of sextortion in the context of romance fraud - Cross, Cassandra (Criminology & criminal justice, 2025)
Romance fraud, where an offender uses the guise of a genuine relationship for monetary gain, affects millions globally. Further to financial losses, evidence suggests victims may also be targeted for sextortion, where the offender either has images or claims to possess indecent images of a person and attempts to extort them for money. Research exploring the association between romance fraud and sextortion is limited, with little known about the characteristics of victims and their potential for financial loss. This article addresses this gap through a quantitative analysis of those who reported romance fraud which included a threat of sextortion. It identifies those who paid in response to the sextortion threat by a variety of situational and demographic variables and locates this group in the broader context of romance fraud. The implications of this study for an understanding of online fraud victimization are explored in detail.